2016
DOI: 10.1186/s40623-016-0415-3
|View full text |Cite|
|
Sign up to set email alerts
|

Volcanic ash in bare ice south of Sør Rondane Mountains, Antarctica: geochemistry, rock magnetism and nondestructive magnetic detection with SQUID gradiometer

Abstract: Nondestructive magnetic detection of tephra layers in ice cores will be an important method to identify and correlate stratigraphic horizons of ice bearing volcanic ash particles. Volcanic ash particles were extracted from tephra-bearing ice samples collected from Nansen Ice Field south of the Sør Rondane Mountains, Antarctica. Particles are fresh glassy volcanic ash with diameters of ~50 μm, and chemical composition of the matrix glass belongs to a low-K basaltic andesite group, ranging from SiO 2 60-62 wt% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…5a for location). By comparing the chemical composition of this volcanic ash with that of other ashes retrieved from major Antarctic ice cores, Oda et al (2016) proposed that the volcanic ashes in the northern part of Nansen C originate from the South Sandwich Islands (for details on geochemical composition ash layers, refer to Table 3 in Oda et al (2016)). The chemical composition of the ashes correlates particularly well with that of ashes from two post-LGM eruptions (see Table 4 in Oda et al (2016)):…”
Section: Nansen Cmentioning
confidence: 99%
“…5a for location). By comparing the chemical composition of this volcanic ash with that of other ashes retrieved from major Antarctic ice cores, Oda et al (2016) proposed that the volcanic ashes in the northern part of Nansen C originate from the South Sandwich Islands (for details on geochemical composition ash layers, refer to Table 3 in Oda et al (2016)). The chemical composition of the ashes correlates particularly well with that of ashes from two post-LGM eruptions (see Table 4 in Oda et al (2016)):…”
Section: Nansen Cmentioning
confidence: 99%
“…ARM increased slightly at water depths greater than 16 m. Although it is not clear whether the ARM carriers were the result of authigenic iron sulfide formation or the deposition of material suspended in the hypolimnion water layer, they suggest that the magnetic properties of the surficial sediments on the lake floor are controlled Open Access *Correspondence: hirokuni-oda@aist.go.jp 1 Geological Survey of Japan, Research Institute of Geology and Geoinformation, AIST, Tsukuba, Japan Full list of author information is available at the end of the article by both their location within the basin and the limnological stratification of the brackish lake water. Oda et al (2016) presented volcanic ash particles extracted from tephra-bearing ice samples collected from the Nansen Ice Field south of the Sør Rondane Mountains, Antarctica. Major element concentrations of the volcanic particles show high similarity with those of tephra layers associated with the South Sandwich Islands in the EPICA-Dome C, Vostok, and Dome Fuji ice cores.…”
Section: Environmental and Rock Magnetism: Applicationsmentioning
confidence: 99%
“…Cicchino et al [10] measured the geochemistry, as well as the magnetic remanence and AMS (anisotropy of magnetic susceptibility), of two islands in the Aeolian Islands to improve the stratigraphic correlation between the deposits cropping out on these two islands. Oda et al [11] carried out rock magnetic and geochemical analyses on volcanic ash particles extracted from tephra-bearing ice samples collected from the Nansen Ice Field south of the Sør Rondane Mountains (Antarctica) and found that the magnetic mineral in the volcanic particles was titanomagnetite with an ulvöspinel content of 0.2-0.35 (in 0 to 1 scale). Oda et al [11] also compared the geochemistry of the volcanic ash with that of three tephra layers from three different locations in Antarctica and found that these samples had a high geochemical similarity.…”
Section: Introductionmentioning
confidence: 99%
“…Oda et al [11] carried out rock magnetic and geochemical analyses on volcanic ash particles extracted from tephra-bearing ice samples collected from the Nansen Ice Field south of the Sør Rondane Mountains (Antarctica) and found that the magnetic mineral in the volcanic particles was titanomagnetite with an ulvöspinel content of 0.2-0.35 (in 0 to 1 scale). Oda et al [11] also compared the geochemistry of the volcanic ash with that of three tephra layers from three different locations in Antarctica and found that these samples had a high geochemical similarity. The source of the tephra layers was suspected to be South Sandwich Island, located 2800 km from the Sør Rondane Mountains.…”
Section: Introductionmentioning
confidence: 99%